A Stylistic Approach to the Novel Ladies of the Moon by Jokha Al Harithi - Mahmoud, AbdullRahman Muhammad (Journal of Tikrit University for Humanities, 2024)
There is no longer any doubt among scholars of literature and criticism that the stylistic approach has become the most capable of critical approaches to analyzing literary discourse in an objective, scientific manner. Stylistics is one of the areas of literary criticism based on its linguistic structure without any other social influences. Or political, intellectual, or anything else, except what this linguistic structure indicates of these influences. Stylistics means studying the text and describing the method of formulation and expression. Therefore, the importance of stylistic analysis appears to be that it reveals the aesthetic connotations in the text by penetrating its content. And analyzing its elements. If it is said: ((Linguistics is the one that studies what is said, then stylistics is the one that studies the manner of what is said, using description and analysis at the same time.)) What is important in the stylistic study is to observe what is generated from the text. Reactions and influence on the mind and conscience of the recipient, and they provide us with critical means that contribute to revealing the writer’s ideas and visions in the fictional text. Hence, this study attempts to reveal the writer’s ideas and social visions in the novel (Ladies of the Moon) by Jokha Al-Harithi, which revolves around the concepts of love and freedom and the victories and defeats between them. It also alludes to the political and social changes in the Sultanate of Oman, meaning that its narrative time extends to the beginning of the last century, through the period of British colonialism, the communist rebellion in Dhofar, and the alliance of the Arab tribes in Jabal Akhdar against the occupation forces and the authority that It was supported at that time, and then the period of political, economic and social transformations after oil production in the seventies of the last century, and the renaissance led by Sultan Qaboos bin Said, which changed the face of the country, which began to respond to the requirements of modernity, and the urban progress that crept even into remote villages and changed their features.